2006
DOI: 10.1007/s10803-006-0262-3
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Cognitive Behavioural Intervention for Anger Management in Children Diagnosed with Asperger Syndrome

Abstract: The purpose of the study described was to evaluate the effectiveness of a cognitive behavioural intervention for anger management with children diagnosed with Asperger syndrome. Forty-five children and their parents were randomly assigned to either intervention or wait-list control conditions. Children in the intervention participated in six 2-h weekly sessions while parents participated in a larger parent group. Parent reports indicated a significant decrease in episodes of anger following intervention and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(100 citation statements)
references
References 21 publications
3
92
0
5
Order By: Relevance
“…This strategy offers a unique opportunity to target these traditionally treatment-resistant behaviors with the development of training programs that aim at promoting emotion regulatory processes (Prizant et al 2003;Sofronoff et al 2007;Scarpa and Reyes 2011). Finally, the availability of such training programs might also decrease the use of pharmacological agents associated with severe side effects (e.g., antipsychotic medications), to reduce disruptive behaviors related to emotion dysregulation, such as irritability, temper tantrums, aggression, or self-injurious behavior (Owen et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This strategy offers a unique opportunity to target these traditionally treatment-resistant behaviors with the development of training programs that aim at promoting emotion regulatory processes (Prizant et al 2003;Sofronoff et al 2007;Scarpa and Reyes 2011). Finally, the availability of such training programs might also decrease the use of pharmacological agents associated with severe side effects (e.g., antipsychotic medications), to reduce disruptive behaviors related to emotion dysregulation, such as irritability, temper tantrums, aggression, or self-injurious behavior (Owen et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the authors reviewed these 168 articles in a more in-depth review and reached a consensus to further exclude 136 articles (70 did not involve participants with an ASD diagnosis, 42 were theoretical papers or secondary reviews, 15 did not include at least one ER measure, and 9 did not involve participants with an ASD diagnosis and were theoretical papers or secondary reviews), resulting in 32 articles that met the criteria and were included in the current review. Reference lists from the 32 studies were also reviewed [see asterisks in reference list for final included studies; specifically, three were ultimately identified through Bal et al, 2010;Mazefsky et al, 2013;Sofronoff, Attwood, Hinton, & Levin, 2007;Van Hecke et al, 2009].…”
Section: Methodsmentioning
confidence: 99%
“…Six of the 64 ER measures were open-ended type measures and were used in 13% of the total studies (n = 4). As shown in Table 1, Beaumont and Sofronoff [2008] and Sofronoff et al [2007], both used the Dylan is Being Teased [Attwood, 2004b], measure of social cognition. Three of the four studies that used open-ended measures used more than one.…”
Section: Methods Of Measurementmentioning
confidence: 99%
“…Social skills programs for higher-functioning children and adolescents Many controlled trials 21,23,24,29,[59][60][61][62][63][64][65] and observational studies 25,26,30,31,[66][67][68][69][70] of social skills programs have been conducted. We conducted several meta-analyses on social skills studies that used similar outcome measures.…”
Section: Lowmentioning
confidence: 99%